Dhoho Street Fashion (DSF): Government Strategy In Creating Brand Image Of Tenun Ikat Bandar Kidul Kediri - Aji Prasojo; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (Universitas 45 Surabaya, 2023)
Dhoho street fashion is held every year, the kediri city government tries to introduce tenun ikat bandar kidul. Tenun ikat bandar kidul is unique because it reflects the culture, tourism and social conditions of the kediri community. Tenun ikat bandar kidul has become a global fashion concern because of its detailed manufacturing process, motifs and colors that reflect kediri's identity. The research was conducted using interviews, direct observation of tenun ikat entrepreneurs in bandar kidul, and the dhoho street fashion event. With the hope that people can wear clothes made from traditional tenun ikat bandar kidul fabric, dhoho street fashion seeks to introduce tenun ikat bandar kidul products to the wider community with the aim of creating a brand image. The results of this research show that the existence of dhoho street fashion which is organized by the government and stakeholders can create a good brand image for tenun ikat bandar kidul.